Impacts of KHALEAD framework on the holistic development of student leaders - Md Nor, Nurur Raudzah; Ab Hamid, Ahmad Rauyani; Abd Wahid, Mimi Syahida; Abdul Aziz, Nurul Azrina; Raja Anuar, Raja Anis Husna; Faisal, Akhtar (CENTRE FOR FOUNDATION STUDIES, INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA, 2024)
Humanizing education has become the main agenda of the International Islamic University Malaysia (IIUM) through its Sejahtera Academic Framework (SAF). One of the missions is to produce Insan Sejahtera who are described as balanced individuals embodied with holistic excellence in both physical and spiritual aspects. As part of the IIUM communities, Mahallah Fatima Al-Majritiya (MFAM) has developed a one-year framework named KHALEAD (Khalifah Leadership) for all appointed student leaders. KHALEAD framework is embedded with Khalifah, Amanah, Iqra’ and Rahmatan Lil Alamin (KhAIR) attributes. This research is aimed at investigating and exploring the impacts of this KHALEAD on student leaders. A self-constructed survey which consisted of closed and open-ended items was distributed to MFAM student leaders. The results were then tabulated, and a textual analysis was conducted to analyse the open-ended items. It can be concluded that the student leaders believe the KHALEAD framework impacted them positively.